SPEECH AND THOUGHT PRESENTATION IN JHUMPA LAHIRI’S “INTERPRETER OF MALADIES” - Isti'anah, Arina (Universitas Muhammadiyah Surakarta, 2018)
This research focuses on analyzing speech and thought presentation in the story by means of stylistic approach proposed by Leech and Short (2007). There are two main objectives in this research: (1) to find out speech and thought presentation techniques used in the story and (2) to figure out how those techniques reveal the characterization of the story. Three types of speech presentation were found in the analysis: Free Direct Speech (FDS) in 56%, Direct Speech (DS) in 41%, and Indirect Speech (IS) in 3%. Indirect Thought (IT) is the only thought presentation found in the data, presented in 15 utterances. Those presentation techniques reveal that Lahiri lets the readers involved in the story. FDS shows that the absence of the narrator in the dialogues is influenced by clarity of the context. By employing IT in the whole thought presentation, Lahiri involves herself in the character’s consciousness. Keywords: speech, thought, presentation, stylistics